Chilean liquefaction case history database. Issue 3 (August 2022) - Montalva, Gonzalo; Ruz, Francisco; Escribano, Daniella; Bastías, Nicolás; Espinoza, Daniela; Paredes, Felipe
This article describes a liquefaction database that contains a summary of 209 liquefaction, non-liquefaction, and marginal case histories compiled from the 2010 Mw 8.8 Maule, 2014 Mw 8.2 Iquique, 2015 Mw 8.3 Illapel, and 2016 Mw 7.6 Melinka earthquakes, where the liquefaction phenomenon caused damage to buildings, bridges, roads, and drainage systems, generating millions in losses at the infrastructure level. The database structure is organized into nine main tables that contain site information, geotechnical tests, and seismic parameters. The main tables include the locations of the sites, surface evidence of liquefaction or absence of them, geotechnical parameters from boreholes, and geophysical and laboratory tests. The database contains 7977 m of standard penetration test logs and 390 m of cone penetration test soundings from 209 sites explored. In addition, the seismic parameters of these earthquakes include ground-motion intensity measures estimated for each site. The information in this database allows a better characterization of the seismic demand and the geotechnical properties of the soil involved in predicting liquefaction triggering in this subduction zone. The data associated with this article are available in DesignSafe, where users can freely download and process data to train or evaluate predictive liquefaction models.